A Novel Design of Mm-Wave Antenna for WBN Use Cases - Sasikala S. (International Journal of Intelligent Systems and Applications in Engineering, 2024)
This research article proposes a novel Computer-Aided Design (CAD) inspired microstrip patch antenna. The antenna is configured in the cross-sectional view of an equilateral triangle-shaped structure, resembling a six-pointed star polygon. It consists of a middle layer made of 1.5-millimeter (mm) thickness of the Rogers substrate material (RT 6010TM) with a dielectric strength of 2.2; an upper layer made of a conductive patch strip (proposed CAD design); and bottom layers made of ground material, both 0.45 millimeters thick with copper conductive materials.The antenna exhibits a resonance frequency of 3.3 GHz with a return loss of 34.02 dB and a Standing Wave Ratio (SWR) of 1.4 dB. It operates in the S bandwidth, ranging from 3 GHz to 3.9 GHz, within the microwave spectrum. This design plays a significant role in high-speed internet connectivity and enables various 5G use cases such as mid-band 5G deployment, Enhanced Mobile Broadband (eMBB), IoT, and machine-to-machine communication. The simulated structure effectively characterizes antenna design parameters including bandwidth, impedance bandwidth, return losses, SWR, gain, and radiation pattern within the S-band microwave spectrum. The Finite Element Method (FEM) proves to be a reliable configuration in CAD design, and the six-pointed star polygon-shaped structure achieves good agreement with a resonance frequency of 3.3 GHz as observed and plotted in the results.Moreover, the proposed CAD-inspired antenna features a compact profile and is highly relevant for 5G use cases.